The Gravitomagnetic Effects in Rapidly Rotating Neutron Stars: A Theoretical Study - Yasrina, Atsnaita; Pramono, Nugroho Adi (Journal of Technomaterial Physics, 2020)
Electromagnetic measurements of a general relativistic gravitomagnetic effect can be done within the conductor embedded in a rotating gravitational object’s spacetime. Neutron stars are rotating gravitational object that have strong magnetic field. The gravitomagnetic effect in a neutron star can be determined from the distribution density in the conductor. Neutron star is assumed as a conductor and it rotates rapidly. The distribution density inside the conductor is obtained from the electromagnetic contravariant tensor and the relativistic rotational speed of the conductor. It has obtained the distribution density inside the conductor for the rapidly rotating neutron star. The results are compared to the slowly rotating neutron star which depends on the angular veolocity and the gravitational field.